Proximate analysis of dairy-free, ready-to-use complementary food developed with MOCAF, mung bean flour, and tempeh flour - Widya Indriani; Rayyane Mazaya Syifa Insani; Darren Delfino (Hasanuddin University Food Science and Technology Study Program, 2025)
Cow’s milk is a common ingredient added to commercial complementary foods (CCFs) as a source of protein. Despite that, 2–7.5% of Indonesian infants are estimated to have cow’s milk protein allergy (CMPA) and are at risk of deficiencies in protein, fat, and micronutrients due to avoiding dairy-contained CCFs. This study aimed to develop a dairy-free, ready-to-use complementary food (RUCF) by utilizing plant-based protein sources. Tempeh flour, mung bean flour, modified cassava flour (MOCAF), sugar, inulin, micronutrient mix, and palm oil were mixed in a low-speed Stephan mixer at 75oC for 15 minutes. The ratios of tempeh flour (TF) and mung bean flour (MBF) were 12:20, 16:16, and 20:12 (w/w). Proximate and micronutrient (vitamin B12, calcium, and zinc) contents were determined and compared to the standard regulation of complementary food by the Indonesian Food and Drug Association (PerBPOM) No. 24/2019. There was no significant difference between the three formulas for energy, moisture, total carbohydrate, and total fat contents (p > 0.05). The formula with a TF-to-MBF ratio of 20:12 had significantly higher ash and protein contents compared to other treatments (p<0.05). In comparison to the standard nutrient content, the fat content of all formulas exceeded the maximum standard of 4.5 g/100 kcal. Furthermore, vitamin B12 content was lower than the minimum standard of 0.05 µg/100 kcal. Although all formulas majorly fulfilled the regulatory range of nutrient content for CCF, product reformulation is necessary to adjust fat, vitamin B12, and other nutrients that has not fulfilled the regulations.